2022
DOI: 10.1128/spectrum.02740-21
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Activity of Imipenem in Combination with Ceftazidime/Avibactam or Avibactam against Non-MBL-Producing Extensively Drug-Resistant Pseudomonas aeruginosa

Abstract: Handling the infections by extensively drug-resistant Pseudomonas aeruginosa (XDRPA) strains is challenging due to their complicated antibiotic resistance mechanisms in immunosuppressed patients with pulmonary diseases (e.g., cystic fibrosis, chronic obstructive pulmonary disease, and lung transplant), ventilator-associated pneumonia, and bloodstream infections. The current study suggested the potentiality of the ceftazidime-avibactam-imipenem combination against XDRPA with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Growth curve was prepared using a previously described method with slight modification. 25 , 26 PAO1 culture was inoculated into 1 mL fresh LB broth at 37 °C with overnight shaking to reach the initial optical density of 0.01 at 600 nm (OD 600 ). Monitoring and recording the OD 600 of each sample was monitored and recorded using an enzyme marker to determine the growth density of culture for up to 36 h. Each experiment was performed using a sterile 96-well U-bottom polystyrene microtiter plate(Wuxi NEST Biotechnology Co., Ltd).…”
Section: Methodsmentioning
confidence: 99%
“…Growth curve was prepared using a previously described method with slight modification. 25 , 26 PAO1 culture was inoculated into 1 mL fresh LB broth at 37 °C with overnight shaking to reach the initial optical density of 0.01 at 600 nm (OD 600 ). Monitoring and recording the OD 600 of each sample was monitored and recorded using an enzyme marker to determine the growth density of culture for up to 36 h. Each experiment was performed using a sterile 96-well U-bottom polystyrene microtiter plate(Wuxi NEST Biotechnology Co., Ltd).…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al demonstrated the efficacy of CZA in combination with imipenem in the treatment of XDR- P. aeruginosa isolates that do not produce MBL but possess porin and AmpC mutations and multidrug efflux pumps and overexpress AmpC enzymes. Although counterintuitive, the efficacy of this combination may be explained by the reduction in the AmpC levels by ceftazidime, which acts as a suicide molecule, and by the inhibition of the AmpC enzymes by avibactam, in addition to the known reduced affinity of imipenem to efflux pumps [ 96 ].…”
Section: Antibiotic Synergy and Treatment Of Carbapenem-resistant Ent...mentioning
confidence: 99%
“…In Pseudomonas aeruginosa, efflux pump overexpression and porin loss contribute to carbapenem resistance. Gram-negative bacteria are generally more resistant due to their cell wall, reduced permeability, efflux pumps, and broad-spectrum b-lactamases (Galani et al, 2021;Zhang et al, 2022). Some traditional treatments may be ineffective, highlighting the need for new antimicrobials to combat these resistant infections (Thaden et al, 2017).…”
Section: Pathogenesis Of Antibiotic Resistance In Carbapenem-resistan...mentioning
confidence: 99%